Phenotypic effects of the Y chromosome are variable and structured in hybrids among house mouse recombinant lines - Martincová, Iva; Ďureje, Ľudovít; Kreisinger, Jakub; Macholán, Miloš; Piálek, Jaroslav (Ecology and evolution, 2019)
Hybrid zones between divergent populations sieve genomes into blocks that introgress across the zone, and blocks that do not, depending on selection between interacting genes. Consistent with Haldane's rule, the Y chromosome has been considered counterselected and hence not to introgress across the European house mouse hybrid zone. However, recent studies detected massive invasion of M. m. musculus Y chromosomes into M. m. domesticus territory. To understand mechanisms facilitating Y spread, we created 31 recombinant lines from eight wild-derived strains representing four localities within the two mouse subspecies. These lines were reciprocally crossed and resulting F1 hybrid males scored for five phenotypic traits associated with male fitness. Molecular analyses of 51 Y-linked SNPs attributed ~50% of genetic variation to differences between the subspecies and 8% to differentiation within both taxa. A striking proportion, 21% (frequencies of sperm head abnormalities) and 42% (frequencies of sperm tail dissociations), of phenotypic variation was explained by geographic Y chromosome variants. Our crossing design allowed this explanatory power to be examined across a hierarchical scale from subspecific to local intrastrain effects. We found that divergence and variation were expressed diversely in different phenotypic traits and varied across the whole hierarchical scale. This finding adds another dimension of complexity to studies of Y introgression not only across the house mouse hybrid zone but potentially also in other contact zones.
Keywords: phenotype variation; Y‐associated effects; wild‐derived strain; Mus musculus domesticus; sperm quality; Mus musculus musculus